Performances of HEART score to predict 6-month prognostic of emergency department patients with chest pain: a retrospective cohort analysis. (5th June 2023) - Fiore, Giorgio; Pinto, Giuseppe; Preda, Alberto; Rampa, Lorenzo; Gaspardone, Carlo; Oppizzi, Michele; Slavich, Massimo; Di Napoli, Davide; Bianchi, Gianluca; Etteri, Massimiliano; Margonato, Alberto; Fragasso, Gabriele
Abstract : Background and importance: Chest pain is a frequent cause of patient admissions in emergency departments (EDs). Clinical scores can help in the management of chest pain patients with an undefined impact on the appropriateness of hospitalization or discharge when compared to usual care. Objectives: The aim of this study was to assess the performances of the HEART score to predict the 6-month prognostic of patients presenting to the ED of a tertiary referral university hospital with non-traumatic chest pain. Design, settings, and participants: From 7040 patients presenting with chest pain from 1 January 2015 to 31 December 2017, after applying exclusion criteria (ST-segment elevation >1 mm, shock, absence of telephone number) we selected a sample of 20% chosen randomly. We retrospectively assessed the clinical course, definitive diagnosis, and HEART score according to ED final report. Follow-up was made by telephone interview with discharged patients. In hospitalized patients, clinical records were analyzed to evaluate major adverse cardiac events (MACE) incidence. Outcome measure and analysis: The primary endpoint was MACE, comprising cardiovascular death, myocardial infarction, or unscheduled revascularization at 6 months. We assessed the diagnostic performance of the HEART score in ruling out MACE at 6 months. We also assessed the performance of ED usual care in the management of chest pain patients. Results: Of 1119 screened, 1099 were included for analysis after excluding patients lost to follow-up; 788 patients (71.70%) had been discharged and 311 (28.30%) were hospitalized. Incident MACE was 18.3% ( n = 205). The HEART score was retrospectively calculated in 1047 patients showing increasing MACE incidence according to risk category (0.98% for low risk, 38.02% for intermediate risk, and 62.21% for high risk). Low-risk category allowed to safely exclude MACE at 6 months with a negative predictive value (NPV) of 99%. Usual care diagnostic performance showed 97.38% sensitivity, 98.24% specificity, 95.5% positive predictive value, and 99% NPV, with an overall accuracy of 98.00%. Conclusions: In ED patients with chest pain, a low HEART score is associated with a very low risk of MACE at 6 months.